(untitled) (Journal of Mathematics Mechanics and Computer Science, 2012)
Here for solving ODE of the second order we construct a new class of hybrid methods of multistep type. Taking into account that implicit methods are more precise we consider a question on definition of implicit character of hybrid methods and construct methods with the order of accuracy p = 6 for k = 2.